MODEL PEMBELAJARAN MULTISENSORI BERBANTUAN APLIKASI KHAN ACADEMY KIDS DALAM MENGATASI KESULITAN MEMBACA PERMULAAN - Novita Nur Anggraini; Nuhyal Ulia (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
Research was conducted to determine whether there was an influence of the multisensory learning model assisted by the Khan Academy Kids application on initial reading difficulties in class I students at SDN Kedalon 03. This research used a quantitative method with a one-group pre test-posttest design. Samples were taken using non-probability sampling with saturated sampling. From a sample of 17 students and students all participated. The results of the data normality test show that the pretest results and posttest results are normal and have an influence on the results of students' initial reading difficulties in Indonesian language subject content. The significance value in the pretest is 0.062 > 0.05, so it can be concluded that the pretest results are normally distributed. The significance value in the posttest was 0.73 > 0.05, and the posttest results were also normally distributed. In the paired sample t – test the sig value. with a result of 0.000 < 0.05. Sig value. (2 – tailed) < α then HO is rejected. So it can be concluded that the multisensory learning model assisted by the Khan Academy Kids application has an effect on initial reading difficulties in Indonesian language subjects for class I students at SDN Kedalon 03.